2018
DOI: 10.1073/pnas.1718931115
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale strain manipulation of a charge density wave

Abstract: SignificanceCharge density waves (CDWs) are simple periodic reorganizations of charge in a crystal, and yet they are still poorly understood and continue to bear surprises. External perturbations, such as strain or pressure, can in principle push a CDW phase into a different ordering geometry. However, engineering this type of quantum criticality has been experimentally challenging. Here, we implement a simple method for straining bulk materials. By applying it to 2H-NbSe2, a prototypical CDW system studied fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 43 publications
3
53
0
Order By: Relevance
“…FeSe presents an excellent playground to explore the interplay of electronic nematicity and symmetry breaking strain due to its structural simplicity and the absence of magnetic ordering that is present in many other Fe-based superconductors 29,30 . In principle, various experimental methods can be used to apply strain to a material, such as voltage-controlled piezoelectric setups 11,13,25,31,32 , mechanical actuators 27 , differential thermal contraction 24,33 , and heteroepitaxial film growth [34][35][36][37] . In this work, we use molecular beam epitaxy (MBE) to grow FeSe thin films (a = 3.8 Å) on SrTiO 3 (001), a substrate with a~2% lattice mismatch (a = 3.9 Å) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…FeSe presents an excellent playground to explore the interplay of electronic nematicity and symmetry breaking strain due to its structural simplicity and the absence of magnetic ordering that is present in many other Fe-based superconductors 29,30 . In principle, various experimental methods can be used to apply strain to a material, such as voltage-controlled piezoelectric setups 11,13,25,31,32 , mechanical actuators 27 , differential thermal contraction 24,33 , and heteroepitaxial film growth [34][35][36][37] . In this work, we use molecular beam epitaxy (MBE) to grow FeSe thin films (a = 3.8 Å) on SrTiO 3 (001), a substrate with a~2% lattice mismatch (a = 3.9 Å) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The height of the corrugation is in the range of tens of picometers, comparably small as that of other stain-induced corrugations [44][45][46] . Without an atomic resolution in this experiment, we cannot make a quantitative analysis of the strain based on precise determination of atomic displacement 34,46 .…”
Section: Resultsmentioning
confidence: 99%
“…7 Physical models also suggest that protruding nanoscale surface domains on nanoparticles can induce sufficient membrane deformation to promote their more efficient engulfment. [16][17][18] Thus, framboidal surface character could be advantageous not only for targeting cancer cells that express SR-B1 but also for enhanced endocytosis. Furthermore, unlike the equivalent smooth nanoparticles, Hu and co-workers 7 demonstrated that nanoparticles comprising protruding nanodomains could bypass endolysosomal compartments and efficiently deliver drugs to the nuclear region.…”
Section: Discussionmentioning
confidence: 99%
“…15 Moreover, protruding nanodomains can induce lipid bilayer deformation, which should in turn enhance the kinetics of cell uptake. [16][17][18] Indeed, nanoscale surface roughness is well-known to promote both protein receptor binding and the intracellular uptake of nanoparticles. 19,20 Furthermore, the Dengue fever virus also possesses pH-sensitive surface domains that undergo conformational changes during infection which facilitate its timely exit from the endosomes.…”
Section: Introductionmentioning
confidence: 99%